Assessments of Arterial Stiffness and Endothelial Function Using Pulse Wave Analysis. (14th May 2012) - Stoner, Lee; Young, Joanna M.; Fryer, Simon
Abstract : Conventionally, the assessments of endothelial function and arterial stiffness require different sets of equipment, making the inclusion of both tests impractical for clinical and epidemiological studies. Pulse wave analysis (PWA) provides useful information regarding the mechanical properties of the arterial tree and can also be used to assess endothelial function. PWA is a simple, valid, reliable, and inexpensive technique, offering great clinical and epidemiological potential. The current paper will outline how to measure arterial stiffness and endothelial function using this technique and include discussion of validity and reliability.